Pyrazole-Based Thrombin Inhibitors with a Serine-Trapping Mechanism of Action: Synthesis and Biological Activity - Calvin Dunker; Lukas Imberg; Alena I. Siutkina; Catharina Erbacher; Constantin G. Daniliuc; Uwe Karst; Dmitrii V. Kalinin (MDPI AG, 2022)
New antithrombotic drugs are needed to combat thrombosis, a dangerous pathology that causes myocardial infarction and ischemic stroke. In this respect, thrombin (FIIa) represents an important drug target. We herein report the synthesis and biological activity of a series of 1H-pyrazol-5-amine-based thrombin inhibitors with a serine-trapping mechanism of action. Among synthesized compounds, flexible acylated 1H-pyrazol-5-amines 24e, 34a, and 34b were identified as potent 16-80 nM thrombin inhibitors, which showed practically no off-targeting effect against other physiologically relevant serine proteases. To prove that synthesized compounds are covalent thrombin inhibitors, the most potent derivative 24e (FIIa IC50 = 16 nM) was studied in a mass-shift assay, where it has been shown that 24e transfers its acyl moiety (pivaloyl) to the catalytic Ser195 of thrombin. Performed herein docking studies also confirmed the covalent mechanism of thrombin inhibition by synthesized compounds. Acylated aminopyrazoles found during this study showed only limited effects on plasma coagulation in activated partial thrombin time (aPTT) and prothrombin time (PT) in vitro assays. However, such thrombin inhibitors are expected to have virtually no effect on bleeding time and can be used as a starting point for developing a safer alternative to traditional non-covalent anticoagulants.